Once a Happy Valley : Memoirs of an ICS Officer in Sindh, 1938-1948 - Pearce, Roger (Karachi Oxford University Press, 2001)
This book recounts the experiences of a British ICS officer on the Indian subcontinent during the last seven years before independence and the first eighteen months after the birth of Pakistan. It provides an invaluable record of British administration in Sindh and includes interesting information about the social activities of British officers and their families living on the subcontinent during the Raj.
This book is essentially a narrative of the experiences of a British ICS officer in the Indian subcontinent during the last seven years before independence and the first eighteen months after the birth of Pakistan, and provides an invaluable record of British administration in Sindh. The author's accounts of the conditions prevailing in rural Sindh in the middle of the twentieth century are based on memory as well as personal notes and letters, and include interesting details of the social activities of British officers and their families living in the subcontinent during the Raj. The story is traced through selection and training in the ICS to posting as Assistant Collector and Deputy Commissioner in Sindh, where the author found true friends among his Sindhi and Baloch neighbours. Finally, as Secretary of Agriculture, the author witnessed the birth of Pakistan-he personally met and shook hands with the founder of Pakistan, Muhammad Ali Jinnah, and Lord Mountbatten- but found himself a foreigner in a land he had considered home.
Include Maps, Illustrations, Glossary and Index.
Keywords: Great Britain -- Pakistan--Sindh -- Pearce, Roger -- Colonial administrators